TREATMENT OUTCOMES OF CONCURRENT CHEMORADIOTHERAPY USING IMRT IN PATIENTS WITH STAGE III AND IVA-B HYPOPHARYNGEAL AND LARYNGEAL CANCER AT HANOI ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe several clinical characteristics and evaluate the treatment response in stage III and IVA-B hypopharyngeal and laryngeal cancer patients treated with concurrent intensity modulated radiation therapy-based chemoradiotherapy with every three-weekly Cisplatin at Hanoi Oncology Hospital.Subject and methods: A cross-sectional study on 56 patients undergoing definitive concurrent chemoradiotherapy with every three-weekly Cisplatin and intensity modulated radiation therapy with a total dose of 66-70 Gy at Ha Noi Oncology Hospital from January 2021 to June 2025.Results: The mean age at diagnosis was 54,8 ± 5,9 years, with a predominance of male patients. The most common reasons for hospitlization were dysphagia and cervical lymphadenopathy. Most cases were diagnosed at stage IVA-B (73.2%). The overall response rate was 96.4%, in which complete response rate was 50% and partial response was 46.4%. Lung metastasis occurred in 3.6% of patients after treatment. The disease stage had a significant association with the treatment response rate.Conclusion: Concurrent intensity modulated radiation therapy-based chemoradiotherapy with every three-weekly Cisplatin for stage III and IVA-B hypopharyngeal-laryngeal cancer at Hanoi Oncology Hospital yielded favorable outcomes with a high treatment response rate.
Keywords: Concurrent chemoradiotherapy, hypopharyngeal and laryngeal cancer, response rate.